2021
DOI: 10.3390/ijerph18052780
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Functioning in Patients with Irritable Bowel Syndrome, Non-Affective Psychosis and Affective Disorders—Differences and Similarities

Abstract: Irritable bowel syndrome (IBS), as part of the functional somatic syndromes, is frequent in the general population. Medical care and morbidity costs are high, and so is the psychological and somatic strain. The etiopathogenesis of IBS is still poorly understood; it is assumed to be multifactorial and to include biopsychosocial factors. Links between the intestine, psyche, nervous system (e.g., via the hypothalamic–pituitary–adrenal axis (HPA-Axis/neurotransmitters) and with the microbiome, the immune system ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 48 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Among the included studies, three compared patients suffering from IBS with patients diagnosed with IBD [26][27][28], while other studies focused on patients with one of these conditions (IBS or IBD) and compared them with a control group [29][30][31][32]. RFS mean (SD) scores were 2.7 (1.4) for IBS, 1.4 (1.9) for NAP, and 3.3 (1.7) for AD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the included studies, three compared patients suffering from IBS with patients diagnosed with IBD [26][27][28], while other studies focused on patients with one of these conditions (IBS or IBD) and compared them with a control group [29][30][31][32]. RFS mean (SD) scores were 2.7 (1.4) for IBS, 1.4 (1.9) for NAP, and 3.3 (1.7) for AD.…”
Section: Resultsmentioning
confidence: 99%
“…There were differences between IBS-M and IBS-C (p = 0.023). No significant differences between IBS-M and IBS-D, and between IBS-D and IBS-C. With regard to the instruments used to assess mentalization, three studies used the Mentalization Questionnaire (MZQ) [26,28,31], two studies used the Metacognitions Questionnaire-30 (MCQ-30) [27,32], one study used both the Reflective Functioning Questionnaire (RFQ) and Reading the Mind in the Eyes Test (RMET) [29], and one study used both the Brief Reflective Function Interview (BRFI) and Reflective Functioning Scale (RFS) [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, the importance of deficits in mentalizing and personality functioning, especially specific structural deficits in affective processing, are empirically well-supported for patients with PSS: In recent studies, patients with IBS showed higher mentalizing deficits than healthy controls ( 4 , 8 ) and patients with inflammatory bowel diseases ( 4 ). Additionally, in gastroenterological patients, the diagnostic B-criterion of SSD was associated with higher mentalizing deficits and deficits in personality functioning according to the Operationalized Psychodynamic Diagnosis System ( 6 ).…”
Section: Empiric Evidence Of Deficits In Mentalization and Personalit...mentioning
confidence: 99%